2022
DOI: 10.1016/j.breast.2022.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of palbociclib plus fulvestrant in advanced breast cancer: Results from a population-based cohort study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
3
2
0
Order By: Relevance
“…In our study, the effectiveness in first-line was substantially lower compared to the PALOMA-2 trial (median PFS of 25 months, median OS of 54 months) [ 9 , 18 , 19 ], which aligns with findings from other real-world studies [ 20 , 26 – 28 ] (Table 2 ). This survival gap may partly be attributed to the strict protocol-specified definition of eligible patients for the PALOMA-2 trial, excluding individuals with poor performance status or extensive visceral disease.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the effectiveness in first-line was substantially lower compared to the PALOMA-2 trial (median PFS of 25 months, median OS of 54 months) [ 9 , 18 , 19 ], which aligns with findings from other real-world studies [ 20 , 26 – 28 ] (Table 2 ). This survival gap may partly be attributed to the strict protocol-specified definition of eligible patients for the PALOMA-2 trial, excluding individuals with poor performance status or extensive visceral disease.…”
Section: Discussionsupporting
confidence: 89%
“…Real-world studies of first-line CDK 4/6 inhibitors combined with endocrine therapies have demonstrated a median PFS ranging from 18.7 to 21.3 months 23 , 24 . The results of PFS in the second line are consistent with those published in the pivotal studies 25 and other real-world data studies 26 . We could conclude that all patients benefit equally regardless of the age at which they receive the treatment, since we have not observed statistically significant differences between age groups.…”
Section: Discussionsupporting
confidence: 89%
“…CDK 4/6 inhibitors were introduced in 2017 for ABC; first represented by palbociclib and soon followed by ribociclib in 2018 and abemaciclib in 2020. Considering only this subgroup, the increase was 40.8 fold, supported by evidence from clinical trials and more recent real-word studies ( Cardoso Borges et al, 2022 ).…”
Section: Resultssupporting
confidence: 62%